Biological control of Sclerotium fruit rot of snake fruit and stem rot of lettuce by Trichoderma sp. T76-12/2 and the mechanisms involved. (August 2019) - Wonglom, Prisana; Daengsuwan, Wilailuck; Ito, Shin-ichi; Sunpapao, Anurag
Abstract: Fruit rot of snake fruit and stem rot of lettuce caused by Sclerotium sp. SZ01 and LS01, respectively, are major diseases causing devastating crop losses. Tichoderma species has been known as an effective biological control agent (BCA) against several plant disease pathogens. This research aimed to select an effective Trichoderma species for controlling both diseases. Five Trichoderma spp. isolates were subjected to primary screening against Sclerotium sp. LS01 and SZ01 by dual culture test. Trichoderma sp. T76-12/2 showed significant inhibitory effects on mycelial growth of Sclerotium sp. LS01 and SZ01 with 81.48% and 78.33% inhibition. The Trichoderma sp. T76-12/2 caused discoloration of Sclerotium sp. mycelia at the contact point. Volatile antifungal bioassay revealed Trichoderma sp. T76-12/2 was superior in inhibiting the growth of Sclerotium sp. by up to 44.44% for LS01 and by 59.52% for SZ01. Gas chromatography-mass spectrometry (GC/MS) was conducted to resolve the volatile organic compounds emitted by Trichoderma sp. T76-12/2, and the results revealed presence of antifungal compounds including alcohol (phenylethyl alcohol) and sesquiterpene (epi-cubenol). Enzyme assay of cell-free culture filtrate showed that the activity of β -1, 3-glucanase was higher than that in control. Application of Trichoderma sp. T76-12/2 spore suspension reduced disease severity index for Sclerotium sp. (LS01 and SZ01) in both lettuce and snake fruit in vivo . Based on these findings, Trichoderma sp. T76-12/2 is an excellent candidate to control fruit rot and stem rot diseases caused by Sclerotium sp., due to its capacity to compete, to produce volatile antifungal compounds and cell-wall degrading enzymes, as well as to reduce the disease severity. Highlights: Trichoderma sp. T76-12/2 inhibit mycelial growth of Sclerotium sp. Trichoderma sp. T76-12/2 release phenylethyl alcohol and sesquiterpene to inhibit Sclerotium sp. β- 1, 3-glucanase produced by Trichoderma sp. T76-12/2 cause morphological change on mycelia of Sclerotium sp. Application of Trichoderma sp. T76-12/2 reduce disease severity index.